2015
DOI: 10.1002/iid3.95
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 and IL‐17A degradation by mast cells is mediated by a serglycin:serine protease axis

Abstract: Mast cells contain large amounts of fully active proteases that are stored in complex with serglycin proteoglycan in their secretory granules. Upon degranulation, such serglycin:protease complexes are released to the extracellular space and can potentially have an impact on the local inflammatory reaction, either through direct effects of serglycin proteoglycan or through effects mediated by its bound proteases. The objective of this study was to address this scenario by investigating the possibility that serg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…5B). This protein is involved in regulating the half-life of cytokines and apoptosis induction (46); the downregulation of this protein may thus also contribute to pathophysiological processes resulting in tumor escalation. Other proteins such as platelet endothelial cell adhesion molecule (PECAM1) and platelet glycoprotein 4 (CD36) were detected with similar levels in all platelets, dem- onstrating that differential regulation was only affecting a few selected proteins.…”
Section: Metabolomics Analyses Of Serum Samples Revealed Downregulatimentioning
confidence: 99%
“…5B). This protein is involved in regulating the half-life of cytokines and apoptosis induction (46); the downregulation of this protein may thus also contribute to pathophysiological processes resulting in tumor escalation. Other proteins such as platelet endothelial cell adhesion molecule (PECAM1) and platelet glycoprotein 4 (CD36) were detected with similar levels in all platelets, dem- onstrating that differential regulation was only affecting a few selected proteins.…”
Section: Metabolomics Analyses Of Serum Samples Revealed Downregulatimentioning
confidence: 99%
“…The pro-inflammatory cytokine IL-6 has been shown to play a significant role in the host control of Giardia infections ( 32 ) and in addition SG-dependent serine-proteases have been shown to be involved in the degradation of IL-6 ( 33 ). With this in mind the serum IL-6 levels was determined with ELISA in the two independent experimental infections [experiment #1 (SG +/+ n = 6, SG −/− n = 6) and #2 (SG +/+ n = 5, SG −/− n = 11)].…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have shown that mast cell serine proteases can proteolytically activate cytokines and chemokines [20][21][22][23][24]. On the other hand, a recent report demonstrated that activated cultured mouse peritoneal mast cells can regulate levels of IL-3, IL-6, IL-13, IL-17A, and eotaxin by releasing serglycin-dependent serine proteases, which mediate the proteolytic degradation of these cytokines and chemokines [25]. Previous in vitro studies with purified human skin-derived mast cells have shown that chymase and cathepsin G released upon FcεRI cross-linking degrade cytokines, such as IL-6 and IL-13, that are co-released from these activated mast cells [7].…”
Section: Discussionmentioning
confidence: 99%